Dry-method diaphragm as well as preparation method and application thereof
Through the mixed treatment of conductive agents, binders and activated carbon and the formation of conductive polymer coating, the problem of increasing the density and thickness of dry diaphragm is solved, the performance and life of electrochemical energy storage devices are improved, and the higher Energy density and capacity.
Patent Information
- Application Number
- CN202411238014.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
AI Technical Summary
There is room for improvement in the compaction density, area specific capacity and thickness of the existing dry diaphragm, and it is difficult for the prior art to make thicker diaphragms to improve electrochemical performance.
The conductive agent, binder and activated carbon are mixed and treated. After fibrosis treatment and granulation, an extruded diaphragm is obtained by extrusion molding, and the conductive polymerization is added after cooling in sodium methylbenzenesulfonate solution and methanol. The monomer is formed to form a conductive polymer coating, and finally a dry membrane is obtained by cleaning and drying.
The compaction density and thickness of the dry diaphragm are improved, the energy density and service life of electrochemical energy storage devices are improved, and the self-discharge and leakage current are reduced, and the capacity and power performance of supercapacitors are improved.
Smart Images

Figure CN119132843A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrochemical energy storage devices, and in particular to a dry-process membrane and a preparation method and application thereof. Background Art
[0002] Supercapacitors are a new type of energy storage device. The principle is that the conductive material can be quickly charged and discharged at the electrode surface-electrolyte interface to achieve energy storage and release. Supercapacitors are mainly composed of electrodes, diaphragms, shells, and electrolyte solutions filled in the device. Among them, the electrodes (including the current collector and the membrane on the surface of the current collector) are the core components of supercapacitors and play a decisive role in the performance of supercapacitors.
[0003] At present, most of the membranes of supercapacitors are made by wet and dry methods. In the membranes prepared by the wet method, the residual solvent causes the self-discharge of the supercapacitor to be large, the leakage current to be large, and the service life is not as long as that of the dry membrane. Therefore, the membranes prepared by the dry method have certain advantages. The dry membrane technology was first applied to the field of supercapacitors. With the rapid development of the secondary battery (for example, lithium battery) industry, the dry membrane technology has also begun to be applied to the field of secondary batteries in recent years.
[0004] However, the compaction density and area specific capacity of the dry-process membranes produced by the existing preparation methods need to be improved. In addition, the thickness of the membranes in the existing technology is about 400 μm at most, and it is impossible to make them thicker because thicker membranes are prone to cracking and powdering, which affects the electrochemical performance. Summary of the invention
[0005] In view of this, the present application proposes a method for preparing a dry-process membrane to improve the compaction density, area specific capacity and thickness of the dry-process membrane.
[0006] In addition, it is also necessary to provide a dry-process membrane prepared by the above-mentioned preparation method and its application.
[0007] An embodiment of the present application provides a method for preparing a dry diaphragm, comprising the following steps: mixing a conductive agent, a binder and activated carbon to obtain a premixed powder; fiberizing the premixed powder to obtain a fiberized powder; granulating the fiberized powder; extruding the granulated fiberized powder to obtain an extruded diaphragm, wherein the thickness of the extruded diaphragm is 500 μm to 1000 μm; preparing a mixed solution, wherein the mixed solution comprises a sodium toluenesulfonate solution and methanol, wherein the concentration of the sodium toluenesulfonate solution is 0.3 mol / L to 0.5 mol / L, and the volume ratio of the sodium toluenesulfonate solution to methanol is (8 to 10): 1; placing the extruded diaphragm in the mixed solution and cooling it to obtain a cooled solution; dissolving a conductive polymer monomer in the mixed solution, and then adding it to the cooled solution to react, so as to form a conductive polymer coating on the surface of the extruded diaphragm; washing and drying the extruded diaphragm after the reaction to obtain the dry diaphragm.
[0008] In one embodiment, the conductive polymer monomer includes pyrrole, aniline, and thiophene. The concentration of the conductive polymer monomer in the mixed solution is 0.1 mol / L to 0.2 mol / L.
[0009] In one embodiment, the conductive agent includes one or more of conductive carbon black, conductive graphite, carbon nanotubes, and graphene.
[0010] In one embodiment, the binder includes one or more of polytetrafluoroethylene, polytetrafluoroethylene derivatives, polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, sodium alginate, polyethylene glycol, and chitosan.
[0011] In one embodiment, the fiberization step is performed in an air flow pulverizer, the air intake pressure of the air flow pulverizer is 1 MPa to 3 MPa, and the pulverization pressure is 1 MPa to 6 MPa.
[0012] In one embodiment, the granulation step is performed in a granulator, the granulation temperature of the granulator is 40° C. to 80° C., and the rotation speed is 20 rpm to 150 rpm. The particle size of the fiberized powder after granulation is 0.2 mm to 5 mm.
[0013] In one embodiment, the extrusion molding step is performed in a roller press, and the temperature of the roller press is 50° C. to 200° C. The roller press comprises at least two rollers, the speed ratio of the two rollers is 0.5 to 8, and the distance between the rollers is 0.5 μm to 2 mm.
[0014] In one embodiment, before the mixing step, the preparation method further comprises: drying the activated carbon at a temperature of 120° C. to 130° C. for 8 h to 12 h.
[0015] An embodiment of the present application provides a dry electrode, which includes a current collector and a dry membrane disposed on the surface of the current collector, and the dry membrane is prepared by the preparation method as described above.
[0016] An embodiment of the present application provides an electrochemical energy storage device, which includes the dry electrode as described above.
[0017] The preparation method of the dry diaphragm of the present application has the advantages of simple process, environmental protection, and low energy consumption. The compaction density of the dry diaphragm of the present application is increased by 15% to 20%, which is beneficial to improving the energy density of electrochemical energy storage devices. The dry diaphragm of the present application also has a relatively high thickness (500μm to 1000μm) while maintaining its stable electrochemical performance, which is beneficial to improving the energy density of electrochemical energy storage devices. The present application deposits a conductive polymer coating on the surface of the diaphragm, and the coating enables the dry diaphragm to have a higher area specific capacity, thereby increasing the capacity of the supercapacitor. The button-type supercapacitor prepared by the dry diaphragm of the present application has a small self-discharge and a small leakage current ratio, which improves the specific energy, specific power and service life of the supercapacitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The present invention is a flowchart of a method for preparing a dry-process membrane according to an embodiment of the present invention. DETAILED DESCRIPTION
[0019] Unless otherwise defined, all technical and scientific terms used herein are identical with the meanings generally understood by those skilled in the art of the technical field belonging to the embodiments of the present application. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present application. In the embodiments, if specific conditions are not specified, they are carried out according to the conditions recommended by normal conditions or manufacturers. If the manufacturer is not specified for reagents or instruments, they are all conventional products that can be obtained by commercial purchase.
[0020] Some embodiments of the present application are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0021] See also Figure 1 In a first aspect, the present application provides a method for preparing a dry film, comprising steps S10 to S80.
[0022] Step S10, mixing the conductive agent, the binder and the activated carbon to obtain a premixed powder.
[0023] In some embodiments, the activated carbon may be dried before the mixing process: the drying temperature is 120°C to 130°C and the time is 8h to 12h. The drying may be performed in an oven. The surface of the activated carbon has many micropores and mesopores (pores with a diameter less than 2nm are called micropores, and pores with a diameter between 2nm and 50nm are called mesopores), which are very easy to retain water. The drying process can remove the residual water in the activated carbon to prevent the existing water from inducing side reactions and affecting the performance of the membrane.
[0024] In some embodiments, the conductive agent may be, but is not limited to, one or more of conductive carbon black (SP), conductive graphite (KS-6), carbon nanotubes, and graphene.
[0025] In some embodiments, the binder may be, but is not limited to, one or more of polytetrafluoroethylene (PTFE), a derivative of polytetrafluoroethylene, polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate, polyethylene glycol (PEG), and chitosan.
[0026] In some embodiments, the conductive agent, the binder and the activated carbon are added to a shear mixer for mixing so that the materials are evenly mixed. The speed of the mixer can be 100 rpm to 8000 rpm, for example, 100, 500, 800, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000 or any value between any two adjacent values above. Further, the speed of the mixer can be 2000 rpm to 5000 rpm.
[0027] In some embodiments, the mass ratio of the conductive agent, the binder and the activated carbon is (0.1-0.3):(0.05-0.08):1.
[0028] Step S20, subjecting the premixed powder to fiberization to obtain fiberized powder.
[0029] In some embodiments, the fiberization step is performed in a jet mill. The jet mill can apply high shear force to the premixed powder. At this time, the fiberizable polymer (e.g., PTFE binder) in the powder is stretched into filaments under the action of high shear force. The formed mesh structure can promote the contact between materials of different particles and form more contact points on the surface of the powder, thereby connecting the conductive agent and the activated carbon particles to each other to achieve a better bonding effect. The powder after fiberization can be in the form of large granular agglomerates, and even large lumps of material exist. The lumps have a certain hardness, which proves that the fiberizable polymer (e.g., PTFE binder) has undergone a high degree of fiberization.
[0030] In some embodiments, the air intake pressure of the air flow mill is 1Mpa to 3Mpa, and the crushing pressure is 1MPa to 6MPa. For example, the air intake pressure may be 1Mpa, 1.5Mpa, 2Mpa, 2.5Mpa, 3Mpa, or any value between any two adjacent values above, and the crushing pressure may be 1Mpa, 1.5Mpa, 2Mpa, 3Mpa, 4Mpa, 5Mpa, 6Mpa, or any value between any two adjacent values above. Within the above pressure range, the fiberization degree of the premixed powder is moderate, and the strength and appearance of the film are good. If the pressure is too high, the fiberized filaments may be re-interrupted, and the problem of particle breakage may also occur, resulting in insufficient strength of the film and an unsightly appearance.
[0031] Step S30, granulating the fibrous powder. The granulation step can obtain fibrous powder with finer and more uniform particles, which can increase the thickness of the extruded membrane obtained subsequently and improve the performance of the dry-process membrane.
[0032] In some embodiments, the granulation step is performed in a granulator. The granulation temperature of the granulator is 40°C to 80°C, and the rotation speed is 20rpm to 150rpm. The particle size of the fiberized powder after granulation is 0.2mm to 5mm, for example, 0.2mm, 0.3mm, 0.5mm, 1mm, 2mm, 3mm, 4mm, 5mm or any value between any two adjacent values above. Further, the particle size of the fiberized powder after granulation can be 0.5mm to 2mm.
[0033] Step S40, extruding the granulated fiberized powder into a film to obtain a membrane.
[0034] In some embodiments, the extrusion molding step is performed in a roller press, which includes at least two rollers (e.g., a front roller and a rear roller). The roller press is heated, and when the target temperature (e.g., 50°C to 200°C) is reached, the granulated fiberized powder is vertically added to the roller press. The parameters are set as follows: the speed ratio of the two rollers is 0.5 to 8, the distance between the rollers is 0.5 μm to 2 mm, and the membrane is obtained after rolling. Within the above parameters, sufficient shear force can be provided during rolling, and it is also beneficial to reduce the friction force on the membrane to reduce defects such as holes, stripes, cracks, etc. that appear during film formation, thereby facilitating the acquisition of a smooth and thicker (500 μm to 1000 μm) membrane.
[0035] Furthermore, the number of rolling can be 1 to 10 times, preferably 3 to 5 times. The temperature of the roller press can be 80°C to 150°C, the speed ratio of the two rollers can be 1 to 5, and the distance between the roller gaps can be 1 mm to 5 mm. The width of the roller gap can be gradually reduced by 0.5 mm to 1 mm each time, and the thickness of the film finally obtained can be 500 μm to 1000 μm.
[0036] Step S50, preparing a mixed solution, which includes a sodium toluenesulfonate solution and methanol. The concentration of the sodium toluenesulfonate solution is 0.3 mol / L to 0.5 mol / L, and the volume ratio of the sodium toluenesulfonate solution to methanol is (8 to 10): 1. For example, the concentration of the sodium toluenesulfonate solution can be 0.3 M, 0.4 M, 0.5 M, or any value between any two adjacent values above. The volume ratio of the sodium toluenesulfonate solution to methanol can be 8, 9, 10, or any value between any two adjacent values above.
[0037] In some embodiments, the concentration of the sodium toluenesulfonate solution is 0.3 mol / L, and p-toluenesulfonic acid (TOSH) is used to adjust the pH thereof to 3. In the mixed solution, the volume ratio of sodium toluenesulfonate to methanol is 9:1.
[0038] Step S60, placing the membrane in the mixed solution and cooling it to obtain a cooled solution.
[0039] In some embodiments, the membrane is immersed in a mixed solution of sodium toluenesulfonate electrolyte solution / methanol (volume ratio of 9:1) and stored in a refrigerator until the solution temperature drops to about 4°C.
[0040] Step S70, dissolving the conductive polymer monomer in the mixed solution, and then adding it to the cooling solution for reaction, so as to form a conductive polymer coating on the surface of the membrane.
[0041] In some embodiments, the conductive polymer monomer may be, but is not limited to, pyrrole (Py), aniline, and thiophene. That is, the conductive polymer coating formed may be polypyrrole, polyaniline, polythiophene, and the like. Further, pyrrole may be used after vacuum distillation. Conductive polymer monomers such as polypyrrole, because they contain N elements, can increase the area specific capacity of the electrode, thereby increasing the capacity of the supercapacitor, and can reduce the self-discharge and leakage current of the supercapacitor.
[0042] In some embodiments, a conductive polymer monomer (e.g., pyrrole) is dissolved in a mixed solution of sodium toluenesulfonate electrolyte solution / methanol, the final concentration of the monomer may be 0.1M to 10M, and then slowly added to the above-mentioned cooled solution for 12 hours. The final concentration of the monomer may be 0.1M, 0.5M, 1M, 2M, 5M, 8M, 10M, or any value between any two adjacent values above.
[0043] Step S80, cleaning and drying the membrane after the reaction to obtain a dry-process membrane.
[0044] In some embodiments, after the reaction, the membrane is taken out and washed alternately with deionized water and ethanol for several times, and then dried in a vacuum oven at 60° C. for 24 hours to obtain a dry membrane with a conductive polymer coating on the surface.
[0045] It is understandable that the step numbering is intended to clearly describe the specific preparation method, and does not mean to limit the order of the steps. For example, step S50 "preparing a mixed solution" can be performed before or after any step of steps S10 to S30, and it does not mean that step S50 can only be performed after step S40.
[0046] The second aspect of the present application provides a dry electrode sheet, which includes a current collector and a dry membrane sheet disposed on the surface of the current collector. The dry membrane sheet is prepared by the preparation method as described above, and the surface of the dry membrane sheet has a conductive polymer coating. The dry membrane sheet can be a positive electrode sheet or a negative electrode sheet, which is not limited by the present application. The current collector can be a conventional or unconventional current collector in the art, which is not limited by the present application.
[0047] The third aspect of the present application provides an electrochemical energy storage device, which includes the dry electrode as described above. The electrochemical energy storage device may be, but is not limited to, a secondary battery and a supercapacitor, and the secondary battery may be, but is not limited to, a lithium ion battery, a sodium ion battery, and the like.
[0048] The present application will be further described below in conjunction with specific embodiments and comparative examples.
[0049] Example 1
[0050] S10, adding the activated carbon to a 120°C oven overnight (10 hours), then adding the dried activated carbon, PTFE (binder), and conductive carbon black (conductive agent) to a shear mixer for mixing at a speed of 5000 rpm to obtain a uniformly mixed premixed powder. The mass ratio of activated carbon, conductive carbon black, and PTFE is 84:6:10.
[0051] S20, adding the premixed powder into a jet mill for fiberization, wherein the air inlet pressure of the jet mill is 2 MPa and the pulverizing pressure is 4 MPa.
[0052] S30, adding the fiberized powder into a granulator for granulation, the granulation temperature is 60°C, and the rotation speed is 100 rpm. After granulation, the particle size of the fiberized powder is approximately 2 mm.
[0053] S40, vertically adding the granulated fiberized powder into a roller press, the parameters of the roller press are: temperature of 150°C, speed ratio of two rollers of 5, and distance between rollers of 5mm. Rolling is performed for 5 times to obtain an extruded film with a thickness of approximately 800 μm.
[0054] S50, preparing a mixed solution of a sodium toluenesulfonate solution and methanol. The sodium toluenesulfonate solution has a concentration of 0.3 mol / L, and its pH is adjusted to 3 with p-toluenesulfonic acid (TOSH), and then mixed with methanol, and the volume ratio of the sodium toluenesulfonate solution to the methanol is 9:1.
[0055] S60, immersing the extruded membrane in a mixed solution of sodium toluenesulfonate / methanol, and storing it in a refrigerator until the temperature of the solution drops to about 4°C.
[0056] S70, dissolving the pyrrole after vacuum distillation in a mixed solution of sodium toluenesulfonate / methanol, wherein the final concentration of pyrrole in the mixed solution is 0.1 M. Then, the mixed solution containing pyrrole is slowly added to a cooling solution (a mixed solution containing an extruded membrane and having a temperature of about 4° C.), and reacting for about 12 hours to form a conductive polymer coating (polypyrrole) on the surface of the membrane.
[0057] S80, after the reaction is completed, the extruded membrane is taken out, washed several times with deionized water and ethanol alternately, and dried in a vacuum oven at 60° C. for about 24 hours to obtain a dry membrane with a conductive polymer coating.
[0058] The dry film of Example 1 was pressed onto the current collector by a vertical hot roller press to obtain the dry electrode of Example 1. The roller pressing pressure was 10T, the roller pressing temperature was 150°C, and the roller pressing line speed was 2m / min to produce a dry electrode with a dry film on one side.
[0059] The dry electrode of Example 1 was tested using a blue electric test cabinet of model M340A. The negative electrode was cut into a disc with a diameter of 8.4 mm, and the positive electrode was cut into a disc with a diameter of 14 mm. Each electrode was weighed, and then the electrode was placed in a vacuum oven and baked for 8 hours (vacuum degree 0.1 MPa, positive electrode 85°C, negative electrode 130°C), and then the dry electrode was assembled with a lithium sheet, a diaphragm, a gasket, and an electrolyte into a CR2016 button battery, and the battery was tested.
[0060] Comparative Example 1
[0061] The difference between Comparative Example 1 and Example 1 is that a drying step is directly performed after step S40, and the film is dried in a vacuum oven at 60° C. for 24 hours to obtain a dry film. The rest is the same as Example 1 and will not be described again.
[0062] The dry film of comparative example 1 was pressed onto the current collector by a vertical hot roller press to obtain the dry electrode of comparative example 1. The roller pressing pressure was 10T, the roller pressing temperature was 150°C, and the roller pressing line speed was 2m / min to produce a dry electrode with a dry film on one side.
[0063] According to the method described in Example 1, the dry-process electrode in Comparative Example 1 was assembled into a CR2016 button battery, and the battery was tested.
[0064] Comparative Example 2
[0065] The difference between Comparative Example 2 and Example 1 is that there is no step S30, and the powder is directly rolled into a film without granulation. The parameters of the roller press are: temperature is 120°C, the speed ratio of the two rollers is 8, and the distance between the rollers is 0.5mm. Rolling is performed 3 times to obtain a film with a thickness of approximately 300μm. The rest is the same as Example 1 and will not be repeated here.
[0066] According to the method described in Example 1, the dry-process electrodes in Comparative Example 2 were assembled into CR2016 button batteries, and the batteries were tested.
[0067] Comparative Example 3
[0068] Comparative Example 3 uses a wet process to prepare an electrode plate. The electrode plate formula is graphite: SP: CMC: SBR = 95.7: 1.0: 1.3: 2.0. A double planetary vacuum mixer is used for batching, and the surface density and compaction density of the wet-process electrode plate finally obtained are consistent with those of Example 1. The specific batching process is as follows:
[0069] Add 39g CMC to 2660g water, rotate at 15rpm, 500rpm, and stir for 10min; then adjust to 30rpm, 2500rpm, stir for 120min, vacuum degree 0.1MPa, and obtain a clear glue solution;
[0070] Add 30g SP, rotate at 15rpm, 500rpm, and stir for 10min; then adjust to 30rpm, 3000rpm, and stir for 180min, with a vacuum degree of 0.1MPa;
[0071] Add 1435.5g activated carbon, rotate at 10rpm, 500rpm, and stir for 10min; then adjust to 20rpm, 1500rpm, and stir for 30min, with a vacuum degree of 0.1MPa; then adjust to 30rpm, 2500rpm, and stir for 180min, with a vacuum degree of 0.1MPa;
[0072] Add water to adjust the viscosity of the slurry, orbit at 20 rpm, rotate at 2500 rpm, stir for 10 min, vacuum degree at 0.1 MPa, and the slurry viscosity is within the range of 2000 mPas to 3000 mPas;
[0073] Add 120g SBR emulsion, rotate at 15rpm, rotate at 500rpm, stir for 30min, and set the vacuum degree to 0.1MPa; then sieve the slurry through a 150-mesh sieve, discharge and coat to obtain a wet-process electrode.
[0074] According to the method described in Example 1, the dry-process electrodes in Comparative Example 3 were assembled into CR2016 button batteries, and the batteries were tested.
[0075] Performance Testing
[0076] The test method of compaction density: First, measure the surface density. Surface density refers to the mass of the material per unit area of the electrode. The calculation formula is: surface density = mass / area. Compaction density = membrane surface density / (electrode thickness-current collector thickness)
[0077] The electrodes of the above-mentioned embodiments and comparative examples are assembled into a supercapacitor, and the capacity calculation formula of the supercapacitor is: C=ε0×εr×A / d, where ε0 is the dielectric constant in vacuum, εr is the relative dielectric constant of the supercapacitor, A is the electrode area of the supercapacitor, and d is the electrode spacing of the supercapacitor.
[0078] The performance test results of the above embodiments and comparative examples are shown in Table 1.
[0079] Table 1
[0080]
[0081] It can be seen from Table 1 that compared with Comparative Examples 1 to 3, the compaction density of the dry diaphragm prepared in Example 1 of the present application is increased by 15% to 20%, which is beneficial to improving the energy density of the electrochemical energy storage device. The present application deposits a conductive polymer coating on the surface of the diaphragm, and the coating enables the dry diaphragm to have a higher area specific capacity, thereby increasing the capacity of the supercapacitor. The button-type supercapacitor prepared by the dry diaphragm of the present application has a small self-discharge and a small leakage current ratio, which improves the specific energy, specific power and service life of the supercapacitor. The preparation method of the dry diaphragm of the present application has the advantages of simple process, environmental protection, and low energy consumption.
[0082] The above descriptions are some specific implementations of the present application, but they are not limited to these implementations in actual application. For ordinary technicians in this field, other variations and changes made according to the technical concept of the present application should all fall within the protection scope of the present application.
Claims
1. A method for preparing a dry film. It is characterized in that The steps include: The conductive agent, the binder and the activated carbon are mixed to obtain a premixed powder; The premixed powder is subjected to a fiberizing treatment to obtain a fiberized powder; granulating the fibrous powder; Extruding the granulated fiberized powder to obtain an extruded film, wherein the thickness of the extruded film is 500 μm to 1000 μm; Preparing a mixed solution, the mixed solution comprising a sodium toluenesulfonate solution and methanol, the concentration of the sodium toluenesulfonate solution being 0.3 mol / L to 0.5 mol / L, and the volume ratio of the sodium toluenesulfonate solution to methanol being (8 to 10):1; placing the extruded film in the mixed solution and cooling it to obtain a cooled solution; dissolving a conductive polymer monomer in the mixed solution, and then adding the monomer to the cooled solution for reaction, so as to form a conductive polymer coating on the surface of the extruded film; The extruded membrane after the reaction is cleaned and dried to obtain the dry-process membrane.
2. The method for preparing a dry film according to claim 1, It is characterized in that The conductive polymer monomers include pyrrole, aniline and thiophene, and the concentration of the conductive polymer monomers in the mixed solution is 0.1 mol / L to 0.2 mol / L.
3. The method for preparing a dry film according to claim 1, It is characterized in that The conductive agent includes one or more of conductive carbon black, conductive graphite, carbon nanotubes, and graphene.
4. The method for preparing a dry film according to claim 1, It is characterized in that The binder includes one or more of polytetrafluoroethylene, polytetrafluoroethylene derivatives, polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, sodium alginate, polyethylene glycol, and chitosan.
5. The method for preparing a dry film according to claim 1, It is characterized in that The fiberization step is carried out in a jet mill, the air intake pressure of the jet mill is 1 MPa to 3 MPa, and the pulverizing pressure is 1 MPa to 6 MPa.
6. The method for preparing a dry film according to claim 1, It is characterized in that The granulation step is carried out in a granulator, the granulation temperature of the granulator is 40° C. to 80° C., and the rotation speed is 20 rpm to 150 rpm; the particle size of the fiberized powder after granulation is 0.2 mm to 5 mm.
7. The method for preparing a dry film according to claim 1, It is characterized in that The extrusion molding step is carried out in a roller press, the temperature of the roller press is 50°C to 200°C, the roller press comprises at least two rollers, the speed ratio of the two rollers is 0.5 to 8, and the distance between the rollers is 0.5 μm to 2 mm.
8. The method for preparing a dry film according to claim 1, It is characterized in that Before the mixing step, the preparation method further comprises: drying the activated carbon at a temperature of 120° C. to 130° C. for 8 h to 12 h.
9. A dry electrode, It is characterized in that The invention comprises a current collector and a dry film arranged on the surface of the current collector, wherein the dry film is prepared by the preparation method according to any one of claims 1 to 8.
10. An electrochemical energy storage device, It is characterized in that Comprising the dry electrode as described in claim 9.
